2022
DOI: 10.1016/j.chest.2021.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Race in Pulmonary Function Testing by Aligning Intent and Evidence With Practice and Perception

Abstract: The practice of using race or ethnicity in medicine to explain differences between individuals is being called into question because it may contribute to biased medical care and research that perpetuates health disparities and structural racism. A commonly cited example is the use of race or ethnicity in the interpretation of pulmonary function test (PFT) results, yet the perspectives of practicing pulmonologists and physiologists are missing from this discussion. This discussion has global relevance for incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 76 publications
0
51
0
Order By: Relevance
“…7,8 Additional arguments against the inclusion of race-corrected equations include the variation of how race is reported by an individual or determined by the provider, the lack of inclusion of multi-racial categories in equations, and the wide variation in spirometry values within racial groups. 7 Recent studies have demonstrated that race-correction in spirometry can lead to misdiagnosis or misclassification of medical diagnoses including asthma and chronic obstructive pulmonary dysfunction for patients. 10,11 Lastly, and importantly, the persistent use of race, a socio-political construct based on the physical appearance of an individual, as a proxy for genetic difference in lung function is wrong.…”
Section: The Limitations Of Current Research and Race-corrected Equat...mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Additional arguments against the inclusion of race-corrected equations include the variation of how race is reported by an individual or determined by the provider, the lack of inclusion of multi-racial categories in equations, and the wide variation in spirometry values within racial groups. 7 Recent studies have demonstrated that race-correction in spirometry can lead to misdiagnosis or misclassification of medical diagnoses including asthma and chronic obstructive pulmonary dysfunction for patients. 10,11 Lastly, and importantly, the persistent use of race, a socio-political construct based on the physical appearance of an individual, as a proxy for genetic difference in lung function is wrong.…”
Section: The Limitations Of Current Research and Race-corrected Equat...mentioning
confidence: 99%
“…Furthermore, factors such as smoking status, childhood respiratory illness, obesity, and environmental exposures to air pollution, known contributors to lung function, are not included in interpretation of results 7,8 . Additional arguments against the inclusion of race-corrected equations include the variation of how race is reported by an individual or determined by the provider, the lack of inclusion of multi-racial categories in equations, and the wide variation in spirometry values within racial groups 7 . Recent studies have demonstrated that race-correction in spirometry can lead to misdiagnosis or misclassification of medical diagnoses including asthma and chronic obstructive pulmonary dysfunction for patients 10,11 .…”
Section: The Limitations Of Current Research and Race-corrected Equat...mentioning
confidence: 99%
“…• Ignores variability in how racial/ethnic groups are defined across social settings/societies. 27 Several arguments have been put forward that oppose the removal of race in spirometry predicted equations 28 include the following:…”
Section: Spirometry and The Relationship To Racial Inequities In Asth...mentioning
confidence: 99%
“…However, these equations have been challenged on the grounds that differences in pulmonary function are the product of racism rather than race. 2 Race-specific equations present these differences as normal, the product of biology rather than of racially mediated differences in prenatal care, early childhood nutrition, health care access, and air pollution exposure. 2 In this issue of CHEST, Holland et al 3 use a systematic review to join this debate.…”
mentioning
confidence: 99%
“…2 Race-specific equations present these differences as normal, the product of biology rather than of racially mediated differences in prenatal care, early childhood nutrition, health care access, and air pollution exposure. 2 In this issue of CHEST, Holland et al 3 use a systematic review to join this debate. The authors identify 10 studies that assess the effect of socioeconomic status (SES) on pulmonary function in Black and White individuals.…”
mentioning
confidence: 99%